"TRU-SANEX": A variation on the EURO-GANEX and i-SANEX processes for heterogeneous recycling of actinides Np-Cm. Issue 13 (1st September 2016) - Carrott, Michael; Maher, Chris; Mason, Chris; Sarsfield, Mark; Taylor, Robin
ABSTRACT: A novel separation process for recovering transuranic actinides has been tested in centrifugal contactors using a surrogate feed solution. This "TRU-SANEX" (transuranic element-selective actinide extraction) process uses solvent extraction between nitric acid and an organic phase containing 0.2 mol/L N, N, N′, N′-tetraoctyl diglycolamide with 0.5 mol/L N, N′-dimethyl-N, N′-dioctylhexylethoxy-malonamide to co-extract actinides and lanthanides followed by separate sections for plutonium–neptunium and americium–curium stripping. Overall, good performance was achieved with good recoveries of plutonium and americium in the products and only small amounts of cross-contamination between products. Decontamination factors for selected lanthanides in the americium–curium product ranged from ~40 to >1300.